The effect of acetylcholine immobilization on the electrochemical properties of thiocholine on boron-doped diamond electrode for chlorpyrifos sensor - Atriardi, Shafrizal Rasyid; Hani, Adinda Muthia; Putri, Gadis (Environmental and Materials, 2024)
Background: The inhibition reactions of acetylcholinesterase (AChE) have been studied to develop chlorpyrifos biosensors. The performance of AChE, both as a free enzyme and when immobilized on avidin-functionalized magnetic beads (aMB), was evaluated for the hydrolysis of acetylthiocholine. Detection was conducted through the oxidation of thiocholine on a boron-doped diamond (BDD) electrode surface. Methods: The study compared the performance of free and immobilized AChE by analyzing their ability to oxidize thiocholine on the BDD electrode surface. The inhibitory effects of chlorpyrifos were assessed by determining IC10 and IC50 values for both enzyme forms. Additionally, the influence of metal ions (Fe²⁺ and Mn²⁺) on AChE activity was investigated to evaluate interference effects. Findings: Free AChE demonstrated superior performance in thiocholine oxidation compared to the immobilized enzyme. In chlorpyrifos detection, free AChE exhibited a significantly lower IC10 value (3.44 × 10⁻⁶ mM) compared to immobilized AChE (12.9 × 10⁻⁶ mM), and its IC50 value (3.8 × 10⁻⁴ mM) was approximately two orders of magnitude lower than that of the immobilized AChE (5.18 mM). Furthermore, AChE exhibited resistance to metal ion interference, with signal losses of 48.7% and 40.8% in the presence of Fe²⁺ and Mn²⁺ ions, respectively. These findings indicate that the immobilization of AChE must be carefully optimized for effective sensor application. Conclusion: The study highlights the superior performance of free AChE in chlorpyrifos detection compared to its immobilized counterpart. Immobilization significantly affects enzyme sensitivity, resulting in higher inhibitory concentration values. Additionally, AChE demonstrated notable resistance to interference from metal ions. These results emphasize the need for careful consideration when immobilizing AChE for sensor applications. Novelty/Originality or this article: This study provides a detailed comparison between free and immobilized AChE in chlorpyrifos biosensing, highlighting the impact of immobilization on enzyme sensitivity and performance. The findings contribute to the development of more efficient biosensors by emphasizing the importance of optimizing enzyme immobilization strategies.